2020
DOI: 10.1212/nxi.0000000000000660
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate vs fingolimod following different pretreatments

Abstract: ObjectiveDespite frequent use of fingolimod (FTY) and dimethyl fumarate (DMF), studies comparing clinical efficacy and withdrawal rates of DMF and FTY concerning different pretreatment situations are rare. The aim of our study was to compare relapse occurrence and withdrawal rates of DMF and FTY in different pretreatment situations.MethodsPatients from 4 European centers were retrospectively identified and followed until the 1st relapse after treatment start or if no relapse occurred for a maximum of 2 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Fingolimod (Gilenya®) is approved as oral treatment for relapsing-remitting (RR) MS [8,9]. Its efficacy could be demonstrated in different phase III studies [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Fingolimod (Gilenya®) is approved as oral treatment for relapsing-remitting (RR) MS [8,9]. Its efficacy could be demonstrated in different phase III studies [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed a lower discontinuation rate for fingolimod than for dimethyl fumarate (IPTW-weighted HR, 0.60; 95% CI, 0.44-0.84). A retrospective study including 732 patients with RRMS (409 taking dimethyl fumarate and 323 taking fingolimod) showed similar results regarding the discontinuation between dimethyl fumarate and fingolimod (29.3% of patients discontinued dimethyl fumarate vs 20.7% in fingolimod; P = .008). However, the study investigators found that dimethyl fumarate was associated with an increased relapse risk compared with fingolimod, with an HR of 1.9 (95% CI, 1.4-2.6) and a higher relapse risk in patients taking dimethyl fumarate who were pretreated with natalizumab compared with those switching to fingolimod (HR, 4.5; 95% CI, 1.9-10.8).…”
Section: Discussionmentioning
confidence: 79%
“…27,28 Ocrelizumab is a B-cell depleting humanized monoclonal antibody, which has shown a significant efficacy in reducing disease activity and MRI progression compared with interferon beta in 2 phase 3 trials. 29,30 However, evidence has been inconsistent regarding the comparative efficacy of these 3 common DMTs after switching from natalizumab, 22,23,31,32 and a direct comparison between them is lacking.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only 6/33 (18%) reached protective antibody levels after two mRNA vaccinations. Further research is needed to identify strategies allowing vaccination under FTY treatment without the risk of a disease reactivation due to a prolonged drug holiday, which is known to occur in patients after stopping FTY [5]. As a limitation, the retrospective nature and small cohort size of our study have to be mentioned.…”
Section: Discussionmentioning
confidence: 97%